Assessing the Dengue Diagnosis Capability Gap in the Military Health System. Issue 8 (1st August 2016) - Pal, Subhamoy; Jasper, Louis E.; Lawrence, Kendra L.; Walter, Maureen; Gilliland, Theron; Dauner, Allison L.; Palys, Thomas J.; Wu, Shuenn-Jue L.
ABSTRACT: Dengue, one of the most widespread infectious diseases, has affected U.S. military readiness throughout history. We explored the dengue diagnosis capability gap by circulating a questionnaire among military end users to determine in what capacity diagnostic test results are needed and how these results would be used at various roles of care in the Military Health System. Results were used to generate target product profiles for potential diagnostic tests. We determined that at far-forward locations, diagnostic tests need to be rugged and easy to use and are primarily needed to inform medical evacuation decisions. In mobile or fixed hospitals, diagnostics can be less portable but must be accurate enough to inform patient care decisions reliably. We then evaluated the suitability of using rapid diagnostic tests and enzyme-linked immunosorbent assays based on published performance characteristics, and we used a model to determine positive and negative predictive values in certain simulated deployments. In far-forward settings, a rapid diagnostic test comprising both antigen- and antibody-based detection can fulfill the capability gap with reasonable accuracy, whereas at higher roles of care immunoglobulin M-enzyme-linked immunosorbent assay was determined to be the most suitable option.